Southeast Asia-China interactions reprint of articles from the Journal of the Malaysian Branch, Royal Asiatic Society - Wade, Geoff (MBRAS reprint, 2007)
The relations between the societies and states of Southeast Asia and China have been of enormous significance to both these regions, extending back for literally thousands of years. This useful single-valume edition of key studies on Southeast Asia-China interactions, which were first published in the 'Journal of the Malaysian Branch of the Royal Asiatic Society' (and its precursors), includes classics such as Wang Gungwu's 'The Nanhai Trade' and Paul Wheatley's 'Geographical Notes On Some Commodities Involved in Sung Maritime Trade'. In this compedium, 18 studies examine political, economic, and social interaction as well as the flows of people and technologies which have tied these regions together over the period.